FALL ARMYWORM BIOLOGICAL CONTROL: EVIDENCE, RESEARCH GAPS, AND IMPLEMENTATION PRIORITIES - Juniarny Waworuntu (Jurnal Sapta Agrica, 2026)
Biological control is increasingly promoted for fall armyworm, Spodoptera frugiperda, but recent evidence remains dispersed from natural-enemy discovery to farmer adoption. Objective: This narrative review synthesized open-access Scopus articles indexed as 2026 publications and available through 2 July 2026, assessing evidence maturity toward implementation. Methods: Of 45 Agricultural and Biological Sciences records, 13 full texts were retrieved; 12 articles were included and synthesized thematically. Results: Parasitoids and entomopathogens showed promising controlled efficacy, but field performance varied. Combining Telenomus remus, Beauveria bassiana, and Metarhabditis rainai increased larval mortality and crop performance, whereas baculovirus products underperformed synthetic insecticides. Major gaps involved multi-season validation, standardized crop and economic outcomes, ecological safety, mass production, and sustained adoption. Conclusion: Research should prioritize translating biological efficacy into reliable, measurable, and scalable management strategies.